2021
DOI: 10.1371/journal.pone.0253596
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain during twin pregnancy with favorable pregnancy outcomes in Japan: A retrospective investigation for new criteria based on perinatal registry data

Abstract: In 2009, the United States Institute of Medicine (IOM) reported the optimal gestational weight gain (GWG) during twin pregnancy based on the pre-pregnancy body mass index (BMI). However, there are ethnic variations in the relationship between GWG and pregnancy outcomes. We aimed to establish the criteria for optimal GWG during twin pregnancy in Japan. The study included cases of dichorionic diamniotic twin pregnancy registered in the Japan Society of Obstetrics and Gynecology Successive Pregnancy Birth Registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
3
11
1
Order By: Relevance
“…found results more similar to ours (multi-centre Japanese cohort,2013Obata et al, 2021]; population-based Chinese cohort usingChinese BMI standards, 2011Chen et al, 2018]), finding lower 25th percentiles of GWG, though the 75th percentiles in the Chinese study varied in relation to the IOM guidelines.…”
supporting
confidence: 84%
“…found results more similar to ours (multi-centre Japanese cohort,2013Obata et al, 2021]; population-based Chinese cohort usingChinese BMI standards, 2011Chen et al, 2018]), finding lower 25th percentiles of GWG, though the 75th percentiles in the Chinese study varied in relation to the IOM guidelines.…”
supporting
confidence: 84%
“…[ 43 , 44 , 45 ]. For example, too low a body weight gain increases the risk of pre-term birth, while an excessive body weight gain—the risk of gestational diabetes and hypertension [ 46 , 47 ]. Both in a singleton and twin pregnancy, the maternal body weight gain also correlates with the newborns’ birth weight.…”
Section: Resultsmentioning
confidence: 99%
“…Both in a singleton and twin pregnancy, the maternal body weight gain also correlates with the newborns’ birth weight. Mothers with a low body weight gain more frequently give birth to small-for-gestational-age infants, while among the newborns of mothers who gained too much weight, macrosomia is more common [ 14 , 46 , 48 , 49 ]. For twin pregnancies, it is suggested that the body weight gain in the individual trimesters of pregnancy can be more important than the total weight gain [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations